2018
DOI: 10.1016/j.chiabu.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and behavioral consequences of child abuse among adolescent girls and boys from Barbados and Grenada

Abstract: The current study used latent class analysis to uncover groups of youths with specific abuse (physical, emotional, and sexual) profiles in and outside the family, and identify how membership in each abuse group is associated with behavioral outcomes. Data were collected among a sample of male (n = 662; M = 13.02 years) and female (n = 689; M = 12.95 years) children and adolescents (9-17 years old) from Barbados and Grenada. Self-report surveys were completed by participants in school settings. Three latent cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Consistent with some studies in this field that used one or two items to measure child maltreatment [19,25,26,27], we used one item with a yes/no response option to assess each type of maltreatment. The children were asked if they had ever experienced (1) physical abuse, such as corporal punishment; (2) emotional abuse, such as shame or intimidation; (3) sexual abuse, such as indecent assault or sexual harassment; and (4) neglect, such as with their ideas or opinions ignored.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with some studies in this field that used one or two items to measure child maltreatment [19,25,26,27], we used one item with a yes/no response option to assess each type of maltreatment. The children were asked if they had ever experienced (1) physical abuse, such as corporal punishment; (2) emotional abuse, such as shame or intimidation; (3) sexual abuse, such as indecent assault or sexual harassment; and (4) neglect, such as with their ideas or opinions ignored.…”
Section: Methodsmentioning
confidence: 99%
“…relationship status, educational achievement, employment status, income level, psychological wellbeing, and loneliness) in adulthood. Based on existing findings that the frequency and patterns of exposure to ACEs differs by sex (Debowska, Boduszek, Sherretts, Willmott, & Jones, 2018; McAnee et al, 2019), we hypothesized that distinct profiles of ACEs would be identified for males and females. Additionally, based on an extensive literature showing that polyvictimization, or exposure to multiple different types of victimizations during childhood (Finkelhor, Ormrod, & Turner, 2007), increases risk for psychosocial problems in later life (Charak et al, 2016;Hovens, Giltay, Spinhoven, van Hemert, & Penninx, 2015), we hypothesized that profiles characterized by multiple different ACE events would be associated with poorer mental health and social and emotional wellbeing outcomes in adulthood.…”
Section: 女性的童年期逆境模式更为复杂: 对成年后心理、社会和情绪结果的影响mentioning
confidence: 99%
“…In the present study, women's experiences of IPV were exacerbated because of a high level of tolerance for violence against women and girls within their families and communities and, the acceptance of early sexualization. This link between violence victimization in childhood and violence acceptance is confirmed through research on attitudes and exposure to abuse among 1400 children in Barbados and Grenada (Debowska et al, 2018) and studies on the prevalence of interpersonal violence (Le Franc et al, 2008). Furthermore, Barrow and Ince (2008) demonstrate that sexual exploitation is strongly associated with children becoming sexually active at a young age.…”
Section: Patriarchy and Constraints On Leaving Violent Relationshipsmentioning
confidence: 91%